2017
DOI: 10.1017/jfm.2016.824
|View full text |Cite
|
Sign up to set email alerts
|

Gap resonance and higher harmonics driven by focused transient wave groups

Abstract: The first and higher harmonic components of the resonant fluid response in the gap between two identical fixed rectangular boxes are experimentally investigated in a wave basin. Gap response is excited by transient wave groups (being based on scaled versions of the autocorrelation function of sea-state spectra, representing NewWaves, the average shape of large waves in a sea state). Several different wave groups with different maximum surface elevations, spectral peak frequencies and bandwidths are used, while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
99
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 122 publications
(103 citation statements)
references
References 23 publications
(33 reference statements)
4
99
0
Order By: Relevance
“…In order to extract the bound waves contained within our measurements, we repeat each experiment with a phase shift of 180 • . By subtracting the out-of-phase tests, it is then possible to separate the second-order sum and difference bound waves after filtering (Baldock, Swan & Taylor 1996;Fitzgerald et al 2014;Mai et al 2016;Zhao et al 2017). Evidently, this technique cannot be applied to field measurements of the Draupner wave.…”
Section: Second-order Bound Harmonicsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to extract the bound waves contained within our measurements, we repeat each experiment with a phase shift of 180 • . By subtracting the out-of-phase tests, it is then possible to separate the second-order sum and difference bound waves after filtering (Baldock, Swan & Taylor 1996;Fitzgerald et al 2014;Mai et al 2016;Zhao et al 2017). Evidently, this technique cannot be applied to field measurements of the Draupner wave.…”
Section: Second-order Bound Harmonicsmentioning
confidence: 99%
“…Although the widely used (Mai et al 2016;Zhao et al 2017;McAllister et al 2018) method of harmonic extraction (Baldock et al 1996;Fitzgerald et al 2014) we use relies on a generalised Stokes expansion and is thus not affected by cubic interactions, it cannot be fully relied on in the event of wave breaking. In our experiments, wave breaking occurs at the crest and not at the corresponding 180 • phase-inverted trough.…”
Section: Second-order Bound Harmonicsmentioning
confidence: 99%
“…In Feng and Bai (2015), it was reported that the free surface nonlinearity does not account for the over-estimation of resonant responses. An experimental study was conducted by Zhao et al (2017) who excited first and higher harmonic components of the resonant response in NewWaves. The unrealistic prediction is related to the small damping near the resonant frequency in potential flow models.…”
Section: Introductionmentioning
confidence: 99%
“…• allows for separation of higher-order harmonics, including for higher-bandwidth signals, in physical experiments (Fitzgerald et al 2014;Mai et al 2016;Zhao et al 2017). We examine these four-phase combinations for spreading tests A.3-4 and A.13 and find that two-and four-phase combinations produce very similar results (see appendix B).…”
Section: Category B -Crossing Testsmentioning
confidence: 93%